Peran Masjid Agung Palembang sebagai Pusat Peradaban Islam di Sumatera Selatan - Darmawan, Candra (Proceedings of International Conference on Da'wa and Communication, 2019)
Palembang Grand Mosque is one of the pillars of the strength of the people of South Sumatra, especially Palembang. This mosque is a representation of Muslims in South Sumatra, both in quantity and quality. Palembang Great Mosque has a role as the center of civilization as in the time of the Prophet Muhammad SAW. The role of the mosque is seen in: first, the process of social change, building the morality of the Ummah in the midst of moral degradation, actively carrying out activities that are spiritual building the Ummah, carrying out educational activities or intellectual activities, conducting religious activities, internalizing the values of worship, values of jihad, values trustworthy, disciplined, exemplary, and sincere, responding to the always dynamic and complex problems of the ummah, implementing the mosque's social functions, resolving conflicts that occur in the community, exercising social control, fostering and developing society, moving the economy of the ummah, optimizing all potentials and resources of the ummah, fostering construction and prosperity of the mosque.